Laser‐Induced Graphenization of PDMS as Flexible Electrode for Microsupercapacitors. Issue 23 (10th November 2021) - Zaccagnini, Pietro; Ballin, Chiara; Fontana, Marco; Parmeggiani, Matteo; Bianco, Stefano; Stassi, Stefano; Pedico, Alessandro; Ferrero, Sergio; Lamberti, Andrea
Abstract: Laser graphenization of polymeric surfaces has emerged as one of the most promising technologies to fabricate flexible electrodes. Unfortunately, despite the large number of materials suitable for laser‐induced graphene (LIG) fabrication, there is a lack of stretchable polymers, hindering the full exploitation of LIG for flexible electronics. Herein, the laser graphenization of polydimethylsiloxane (PDMS), the most exploited elastomeric substrate for flexible electronic device fabrication, is proposed for the first time. The low carbon content and the absence of aromatic structures strongly limit the graphenization process resulting in limited conduction properties. Nevertheless, by adding triethylene glycol (TEG) as carbon source into the PDMS matrix, it is possible to improve the graphenization and to reduce the sheet resistance of the written LIG by two orders of magnitude down to 130 ohm sq −1 . The PDMS‐TEG material becomes a suitable candidate for flexible microsupercapacitor fabrication with specific capacitance values as high as 287 µF cm −2 and energy and power density approaching LIG‐based supercapacitors fabricated onto traditional polyimide substrates. Abstract : Laser graphenization of polydimethylsiloxane (PDMS) is first demonstrated and optimized by adding triethylene glycol as carbon source into the PDMS matrix. This strategy allows to improve the graphenization and to reduce the sheet resistance of the written laser‐induced graphene (LIG) by two orders of magnitude. A flexible microsupercapacitor is fabricated with power density approaching LIG‐based supercapacitors onto polyimide substrate.